Analysis of opportunities and challenges presented by big data in climate change research and its social impact. (25th August 2021) - Mangal, Prateek; Rajesh, Anupama; Misra, Richa
The fourth industrial revolution has come at a cost; our planet earth is enduring concurrent changes in population, infrastructure, natural resources etc. and its cumulative ill effects on global climate. These changes coupled with advancements in technology viz. sensors and data mining techniques have led to a growth in study of climate data. Climate change study is a data intensive subject which has seen numerous innovations in data collection methods, and study of that data using big data analytics. The study of climate change and its effects has been one of the top priorities in big climate data analytics implementations. However, the study of climate data by recent methods has revealed several challenges previously unrecorded in data mining literature. The purpose of this paper is to provide an overview of use of big data in climate change research and the opportunities and challenges pertaining to it and its social impact.